Overlap of Psoriatic Arthritis and Dermatomyositis - Christopher Schreiber MD; Melanie Khamlong MD; Nadia Raza MD; Bao Quynh Huynh MD (SAGE Publishing, 2021)
Psoriatic arthritis is an inflammatory arthritis, most commonly occurring several years after the onset of psoriasis. Psoriatic arthritis is associated with many comorbidities, including diabetes mellitus, nonalcoholic fatty liver disease, fibromyalgia, and cardiovascular disease. Dermatomyositis is an inflammatory myopathy primarily affecting the skin and muscles. As per literature review, cases of psoriasis and dermatomyositis have been reported. In most published cases, the courses of these diseases develop independently. This is the case of a 45-year-old woman initially diagnosed with psoriatic arthritis who developed concurrent dermatomyositis. The methods used were PubMed search and UpToDate search.